HR Development, Work Engagement and Organizational Commitment to Analyst and Assistant Performance Sales of PT. Bank Negara Indonesia (Persero) - Esha Siomi Syafril (Enrichment : Journal of Management, 2022)
This study has a purpose, namely to examine the effect of human resources development, work engagement and organizational commitment on the performance of Analysts and Sales Assistants of PT. Bank Negara Indonesia (Persero), Tbk Areas of West Sumatra, Riau and Riau Islands. The data analysis method used in this research is using the SEM (Structural Equation Modeling) method. The research data processing was carried out using the SmartPLS 4 application. The results showed that: 1) Human resources development has a positive and significant effect on performance of analysts and sales assistants of PT. Bank Negara Indonesia (Persero), Tbk Area of ​​West Sumatra, Riau and Kepri, 2) Work engagement has a positive and significant effect on the performance of analysts and sales assistants of PT. Bank Negara Indonesia (Persero), Tbk Area of ​​West Sumatra, Riau and Riau Islands, 3) Organizational commitment has a positive and significant effect on the performance of analysts and sales assistants of PT. Bank Negara Indonesia (Persero), Tbk Areas of West Sumatra, Riau and Riau Islands.